Primitive liposarcoma of the breast. Communication of a clinical case and review of the literature - Krygier, Gabriel; Melgar, Silvia; El Ters, Escandor; Santini, Alejandro; Carzoglio, Julio (Cirugía del Uruguay, 1998)
Primary sarcomas of the breast are extreme/y rare tumors, representing less than 1 % of breast tumors (this can reach 4% if phylloides cystosarcoma is included). A case of primitive liposarcoma of the breast in a 40 year o/d fema/e is presented; diagnostic difficulties and pathology features are pointed out as we/1 as therapeutica/ and prognosis